Dobre maniery seryjnego zabójcy, czyli o konsumpcji lęku - Watters, John (Er(r)go. Teoria - Literatura - Kultura, 2002)
John Watters The Manners of Mass Murder: Eating Fear Summary The article attempts to show, through a close reading of Brett Easton Ellis's American Psycho, the fallacious basis of two currents in late-capitalist discourse. Firstly, through an extension of the theories of Roland Barthes on fashion, that consumer society provides the consumer with extended choice. Secondly, that the refinement of uniquely human behaviour, in this case manners, leads to moral superiority. Ellis's novel presents the reader with a sophisticated murderer who destroys choice through following fashion and manners through acts of violence. It is the author's contention, following Bataille, that the enhancement of uniquely human qualities cannot be the basis for a morality as it encompasses eroticism, perversion and murder.